Specifying a Domain Speciﬁc Language for Simplifying the Authoring of Digital TV Applications - Terças, Lucas de Macedo; Moraes, Daniel de S.; Soares Neto, Carlos de Salles (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
The Brazilian Terrestrial Digital TV System (SBTVD-T) uses the NCL language for multimedia application’s authoring. Although such language has been designed to be easy to understand by producers of such applications, the fact of being XML based introduces a reasonable level of verbosity, which hinders or delays more experienced software developers. This paper proposes sNCL (simpler NCL) a domain speciﬁc language (DSL) focused on the reduction of verbosity in the construction of NCL documents. The sNCL approach does not act as a replacement to the use of NCL, but facilitates its use. Therefore, this scientiﬁc initiation research also proposes the development of a compiler, which generates the ﬁnal NCL document from a sNCL document. This compiler will be implemented in Lua with LPeg library, generating a symbol table, where each table identiﬁer corresponds to a diﬀerent identiﬁer of the XML elements to be generated in the ﬁnal document. The compiler development process will be guided by Test Driven Development (TDD), which ensures a lower probability of errors.